Analisis Strategi Kepemimpinan Kepala Sekolah Dalam Mengimplementasi Progam Tahfizh Al-Qur’an Di SMP Muhammadiyah 1 Blora - Husain, Muhammad Hafid Al; Mustofa, Triono Ali (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to determine the principal's leadership strategy in the implementation of the Qur'an Tahfizh program at SMP Muhammadiyah 1 Blora. The scope of this research includes participatory planning and implementation, leadership methods in monitoring and evaluating the program, as well as the obstacles faced and the solutions taken. The research, which was conducted using a qualitative approach with a case study design, collected data through in-depth interviews with the principal, observation, and document review. The results showed that the principal applies visionary and transformational leadership styles that refer to the principles of Emaslin (Entrepreneur, Manager, Administrator, Leader, and Motivator). The Tahfizh program that started in 2015 is divided into two tracks: regular with a minimum target of 1 juz and dormitory with a target of 15 juz. Program management strategies include vision-mission adjustment, integration into the curriculum, collaboration with credible institutions (PUTM and Pondok Gontor), use of the Ummi method, and periodic evaluation every three months in collaboration with UMMI Korda Blora. The main challenges of implementation include decreased student motivation, limited tuition fees, difficulties in dormitory adaptation, and managing stakeholder expectations. The principal overcame these challenges through program flexibility, a cross-subsidy system, active communication with parents, and comprehensive evaluation through munaqasyah and daily tasmi'. The success of the program was demonstrated by 6 out of 44 boarding students (13.6%) successfully completing 30 juz of memorization. This research underscores the importance of adaptive and student-centered leadership in implementing innovative Islamic education programs. The Tahfizh program is integrated with the school's vision of creating “Cemara” graduates (smart, independent, and morally good), reflecting a holistic approach in Islamic education.